Marked brain asymmetry with intact cognitive functioning in idiopathic Parkinson's disease: a longitudinal analysis. Issue 3 (3rd April 2017) - Tanner, Jared J.; Levy, Shellie-Anne; Schwab, Nadine A.; Hizel, Loren P.; Nguyen, Peter T.; Okun, Michael S.; Price, Catherine C.
Abstract: Objective: A 71-year-old (MN) with an 11-year history of left onset tremor diagnosed as Parkinson's disease (PD) completed longitudinal brain magnetic resonance imaging (MRI) and neuropsychological testing. MRI scans showed an asymmetric caudate nucleus (right < left volume). We describe this asymmetry at baseline and the progression over time relative to other subcortical gray, frontal white matter, and cortical gray matter regions of interest. Isolated structural changes are compared to MN's cognitive profiles.Method: MN completed yearly MRIs and neuropsychological assessments. For comparison, left onset PD ( n = 15) and non-PD ( n = 43) peers completed the same baseline protocol. All MRI scans were processed with FreeSurfer and the FMRIB Software Library to analyze gray matter structures and frontal fractional anisotropy (FA) metrics. Processing speed, working memory, language, verbal memory, abstract reasoning, visuospatial, and motor functions were examined using reliable change methods.Results : At baseline, MN had striatal volume and frontal lobe thickness asymmetry relative to peers with mild prefrontal white matter FA asymmetry. Over time only MN's right caudate nucleus showed accelerated atrophy. Cognitively, MN had slowed psychomotor speed and visuospatial-linked deficits with mild visuospatial working memory declines longitudinally.Conclusions : This is a unique report using normative neuroimaging and neuropsychology to describe an individual diagnosed with PD who had striking striatal asymmetry followed secondarily by cortical thickness asymmetry and possible frontal white matter asymmetry. His decline and variability in visual working memory could be linked to ongoing atrophy of his right caudate nucleus.